The assessment of environmental sustainability: The role of research and development in ASEAN countries. (18th January 2022) - Mehmood, Usman; Askari, Muhammad U.; Saleem, Mubeen
Abstract: Considering the set targets of the Association of Southeast Asian Nations (ASEAN) to increase research and development (R&D) expenditures, this study probes the long‐term and causal association between renewable energy (RE), nonrenewable energy (NRE), economic growth (GDP), and ecological footprints (EFs) in the context of the environmental Kuznets curve (EKC). Empirical evidence is based on the panel data throughout the period 1990–2016 for the selected six ASEAN economies. The Westerlund co‐integration test confirms the long‐run association between R&D, RE, NRE, GDP, and EF. The results of Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) confirm the presence of EKC and show that R&D expenditures lower EF significantly. A 1% increase in R&D and RE decreases EF by 0.01% and 0.27%, respectively. Moreover, a 1% increase in GDP and NRE increases EF by 5.52% and 0.17%, respectively. This means that investment in R&D will enhance air quality by lowering EF in estimated panel countries. Moreover, NRE consumption and GDP increase EF. The panel causality results confirm the bidirectional association between GDP, RE use, R&D expenditures, and EF. To achieve a desirable goal of a clean environment, R&D expenditures hold a strong position for ASEAN countries. This finding should encourage governments to involve public and private investments in R&D programs for energy efficiency. Integr Environ Assess Manag 2022;18:1313–1320. © 2021 SETAC Key Points: Investment in research and development will enhance air quality by lowering ecological footprints in estimated panel countries. The panel causality results confirm bidirectional association between GDP, renewable energy use, R&D expenditures, and EF.